STUDENTS’ PERCEPTION ON THE USE OF SOCRATIVE IN THE MIDDLE TEST - viriana viriana; nurul hakimah (STKIP PGRI SIDOARJO, 2020)
Due to the Covid 19 pandemic, teachers are forced to be able to integrate technology into the classroom to ensure the teaching learning continuity, since the face to face in the classroom is not possible during pandemic. Thus, Socrative is used to conduct the middle test. The online examinations are used as a solution to make the school program still go on. This study focuses on students’ perceptions on the use of Socrative in the middle test.. The research involved 80 participants consisting of 42 students of 8th and 38 students of 7th class from SMPN 48 Surabaya East Java. The data were collected through questionnaires and were analyzed to get the students perception. The results of the study indicated that majority of participants considered the use of Socrative in the middle test practical, effective and efficient in terms of time. Although slow-speed internet is considered to be one of difficulties in using Socrative, most of the participants agreed that the examination online enable them to get new and powerful learning experience.